Intracerebroventricular Infusion of Vasoactive Intestinal Peptide Rescues the Luteinizing Hormone Surge in Middle-Aged Female Rats - Sun, Yan; kyei, Kwame; Shu, Jun; Neal-Perry, Genevieve (Frontiers in Endocrinology, 2012)
Reproductive aging is characterized by delayed and attenuated luteinizing hormone (LH) surges apparent in middle-aged rats. The suprachiasmatic nucleus (SCN) contains the circadian clock that is responsible for the timing of diverse neuroendocrine rhythms. Electrophysiological studies suggest vasoactive intestinal peptide (VIP) originating from the SCN excites gonadotropin-releasing hormone (GnRH) neurons and affects daily patterns of GnRH-LH release. Age-related LH surge dysfunction correlates with reduced VIP mRNA expression in the SCN and fewer GnRH neurons with VIP contacts expressing c-fos, a marker of neuronal activation, on the day of the LH surge. To determine if age-related LH surge dysfunction reflects reduced VIP availability or altered VIP responsiveness under estradiol positive feedback conditions, we assessed the effect of intracerebroventricular (icv) VIP infusion on c-fos expression in GnRH neurons and on LH release in ovariohysterectomized, hormone-primed young and middle-aged rats. Icv infusion of VIP between 1300 and 1600 h significantly advanced the time of peak LH release, increased total and peak LH release, and increased the number of GnRH neurons expressing c-fos on the day of the LH surge in middle-aged rats. Surprisingly, icv infusion of VIP in young females significantly reduced the number of GnRH neurons expressing c-fos and delayed and reduced the LH surge. These observations suggest that a critical balance of VIP signaling is required to activate GnRH neurons for an appropriately timed and robust LH surge in young and middle-aged females. Age-related LH surge changes may, in part, result from decreased availability and reduced VIP-mediated neurotransmission under estradiol positive feedback conditions.